2015
DOI: 10.1097/tme.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Moral Distress, Level of Practice Independence, and Intent to Leave of Nurse Practitioners in Emergency Departments

Abstract: The aims of this research study were to investigate moral distress among emergency department (ED) nurse practitioners (NPs) and examine relationships between moral distress and level of practice independence as well as intent to leave a position. Moral distress has been studied regarding registered nurses and physicians (MDs) but less so in NPs. It is important to explore moral distress in NPs because they tread a unique path between nursing and physician roles. Moral distress may play a significant role in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 32 publications
5
66
0
10
Order By: Relevance
“…In agreement with this study, national and international studies found elevated levels of moral distress in nurses who participated in situations of pain and suffering for patients undergoing life prolonging procedures, with no evidence of success (7)(8)(15)(16)(17)(18)(19) . The professionals had feelings of incapacity when carrying out their procedures and of violation of their ethical principles, which shows situations of great emotional vulnerability (17)(18) .…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In agreement with this study, national and international studies found elevated levels of moral distress in nurses who participated in situations of pain and suffering for patients undergoing life prolonging procedures, with no evidence of success (7)(8)(15)(16)(17)(18)(19) . The professionals had feelings of incapacity when carrying out their procedures and of violation of their ethical principles, which shows situations of great emotional vulnerability (17)(18) .…”
Section: Discussionsupporting
confidence: 64%
“…Studies with nurses practicing at hospital context in various countries found that working with health professionals seen as insecure strongly influences experiences of moral distress, decreasing decision-making capacity (6,(16)(17)(18)(19)(20) . The main negative characteristic perceived in the work context was lack of ability of technical and scientific competence, which are crucial for conducting specific health activities (16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, despite their desire to leave, only a small portion effectively leaves their working position and most remain in their jobs for various contextual factors, such as shortage of other jobs (37) . This reality requires that researchers, managers and nursing leaders work together to identify and implement strategies to deal with the psychic and moral exhaustion of health workers in order to improve retention and job satisfaction (38) . Nurses in leading positions, such as managers, would be more likely to experience psychic and moral exhaustion mainly because of the inherent complexity in the decisionmaking process that involves expectations of the organization, patients, and workers (39) .…”
Section: Discussionmentioning
confidence: 99%